Analisis Kemampuan Berpikir Kritis Peserta Didik Kelas V pada Mata Pelajaran IPAS SDN 1 Bandung Kabupaten Tulungagung - Zulia Rahma Rahayu; Alik Mustafidal Laili (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Education is a conscious and planned effort to create a learning atmosphere and process to enable students to actively develop their potential to possess strength, spirituality/religion, self-control, personality, intelligence, noble character, and the skills they possess for themselves, the community, the nation, and the state. Critical thinking is a cognitive process undertaken by students to systematically and thoroughly analyze a problem, carefully distinguish the problem, and identify and evaluate information in order to formulate problem-solving strategies. This study aims to analyze students' critical thinking abilities. The subjects of the research are fifth-grade students of SDN 1 Bandung, totaling 19 students. Data collection techniques include tests, interviews, and documentation. The data is analyzed using individual qualitative descriptive methods and per indicator. The research results show that students' critical thinking abilities are categorized into high, medium, and low levels. There are 47.38% of students in the high critical thinking category, 26.31% in the medium critical thinking category, and 26.31% in the low critical thinking category.